ANALISIS PENENTUAN KARAKTERISTIK DAN KRITERIA PINJAMAN TANPA BUNGA PADA PERUSAHAAN INTRAGRUP DARI SISI PERPAJAKAN - Rahayuningtias, Niken Rogo; Andriani, Arifah Fibri (JURNAL INFO ARTHA, 2015)
Interest free loans between intragroup companies who have a special relationship is a transaction that is prevalent in the business world. However, in terms of taxing, these transactions require restrictions in order to prevent tax avoidance efforts. One form of tax avoidance is transfer pricing schemes. No exception to the interest-free loan transactions.Therefore,need to be assessed arm's length principle on thistransaction usingfunctional analysisandcomparabilityanalysis. Fielddata indicatea dispute between the taxpayer with the tax officer in determining the characteristics of the interest-free loan, criteriaof the interest-free loans that reflects the arm's length transaction, and the determination offinancial distress as one of the criteria of interest-free loan. This research aims to settlethedisputesubject. The results of this research showed that the characteristics of the interest-free loan can be seen from its character as a loan and the characters that sets it apartfrom the capital. Criteria of interest-free loan in Indonesia have already reflects the arm's length transaction in accordance to intercompany loan functional analysis. A company in financial distress can receive interest-free loan if the company is in a state of insolvency.